2011
DOI: 10.1111/j.1469-7610.2011.02479.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Conceptualising functional impairment in children and adolescents

Abstract: Functional impairment is a key factor in the clinical importance of mental health problems in children. Yet, the nature of impairment and criteria for defining and assessing impairment in childhood disorders has been surprisingly overlooked in much of the literature. The current article examines the extant literature on the conceptualisation, nature and assessment of impairment in childhood disorders. Relations between diagnostic symptoms and functional impairment are discussed together with the influence of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 72 publications
(136 reference statements)
2
97
0
2
Order By: Relevance
“…Clinical samples may be less suited for the investigation of gender differences, because girls with ADHD are referred for treatment less frequently than boys are (44). Thus, the effects of gender on impairment related to ADHD still seem somewhat ambiguous (44), and direct comparison across studies seems to be a problem, because gender effects will partly hinge on the referral source, the rater source, the ages of the children studied, and which functional domains were examined (45).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical samples may be less suited for the investigation of gender differences, because girls with ADHD are referred for treatment less frequently than boys are (44). Thus, the effects of gender on impairment related to ADHD still seem somewhat ambiguous (44), and direct comparison across studies seems to be a problem, because gender effects will partly hinge on the referral source, the rater source, the ages of the children studied, and which functional domains were examined (45).…”
Section: Discussionmentioning
confidence: 99%
“…29 Predictors of functional impairment include experiencing anxiety with stressful situations, 30 and previous research has revealed the association between functional impairment and depression and mental health problems. [31][32][33] The purpose of this study was to empirically test whether siblings of children with disability have higher levels of functional impairment compared with a peer group of children with typically developing siblings.…”
Section: Resultsmentioning
confidence: 99%
“…Functional impairment is a key indicator for the need for mental health services 33 and, as such, early assessment and interventions to limit increasing severity and short-to long-term consequences need to be addressed. When time and attention are disproportionately spent on the child with disability, early signs of functional impairment problems in typically developing siblings may be overlooked or dismissed.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming such factors are not present, First then provides a & Thomas H. Ollendick tho@vt.edu set of decision trees and tables to help one determine the specific diagnoses that are present and which diagnosis is likely the primary one that should be targeted or prioritized for treatment. With this approach, the primary diagnosis is the one that the clinician determines to be most severe or impairing [5]. While guidelines recommended by First [4] are often utilized in clinical settings, there has been variability in how clinical research studies have defined the primary diagnosis.…”
Section: Introductionmentioning
confidence: 99%